2022
DOI: 10.3390/nano12060893
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fluorinated Ionic Liquids on Human Phenylalanine Hydroxylase—A Potential Drug Delivery System

Abstract: Phenylketonuria (PKU) is an autosomal recessive disease caused by deficient activity of human phenylalanine hydroxylase (hPAH), which can lead to neurologic impairments in untreated patients. Although some therapies are already available for PKU, these are not without drawbacks. Enzyme-replacement therapy through the delivery of functional hPAH could be a promising strategy. In this work, biophysical methods were used to evaluate the potential of [N1112(OH)][C4F9SO3], a biocompatible fluorinated ionic liquid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The development of functionalized, bioprivileged, task-specific FILs was previously achieved through the increasing of the perfluoroalkyl sulfonate anion chain ([C F SO ] or greater) [ 37 , 67 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. These FILs have demonstrated distinct transitions associated with the formation of stable self-assembled structures, which might explain its complete miscibility in water [ 71 ].…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The development of functionalized, bioprivileged, task-specific FILs was previously achieved through the increasing of the perfluoroalkyl sulfonate anion chain ([C F SO ] or greater) [ 37 , 67 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. These FILs have demonstrated distinct transitions associated with the formation of stable self-assembled structures, which might explain its complete miscibility in water [ 71 ].…”
Section: Results and Discussionmentioning
confidence: 99%
“…The FILs, based on the [C F SO ] anion implemented in this study, demonstrated to be biocompatible and non-toxic in four human cell lines (Caco-2, HepG2, EA.hy926, and HaCaT) and aquatic species with different biological organization levels ( Vibrio fischeri , Daphnia magna , and Lemna minor ) [ 72 , 73 ]. The effects of these biocompatible FILs using lysozyme, BSA, human phenylalanine hydroxylase, and IFN- 2b as model proteins [ 37 , 74 , 75 , 76 , 77 ] were evaluated, proving the [C F SO ]-based FILs as promising potential biomaterials for drug delivery systems using therapeutic proteins. The formation of aqueous biphasic systems using these biocompatible FILs, based on perfluoroalkyl sulfonate anions, was first proposed by one of the authors [ 54 ] as an extractive platform, proving its potential for the efficient and selective extraction of food colorants.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that the self-assembled structures of FILs have strong interactions with BSA, and they can be considered a promising potential novel biomaterial for drug delivery systems using therapeutic proteins [ 43 ]. Recently, the study of the interactions between FILs and human phenylalanine hydroxylase protein has also demonstrated the encapsulation of the protein by the FIL aggregates [ 44 ]. Therefore, the encapsulation and stabilization of therapeutic proteins using FILs have demonstrated to be a promising strategy to overcome the handicaps in the delivery of therapeutic proteins in the human body, allowing the improvement of their bioavailability, safety, and efficacy by preserving the structure, stability, and biological activity of several different biomolecules.…”
Section: Introductionmentioning
confidence: 99%